FEMALE ATHLETE TRIAD PADA ATLET PUTRI DI PUSAT PENDIDIKAN LATIHAN (PUSDIKLAT) RAGUNAN JAKARTA - Ratu Saputri, Gita Ayu Rosalinda; Dieny, Fillah Fithra (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background: Female athletes tend to consume improper for supporting their performance, so that can impact eating disorder. Eating disorder can lead menstrual irregularity and osteoporosis for them, so they have risk of female athlete triad. The aimed of this study to determine prevalence of female athlete triad in education and training centre (PUSDIKLAT) Ragunan Jakarta. Methods: Descriptive research with cross sectional design, and calculation of total subject used stratified proportional random sampling. The sample was composed of 65 female athletes in Education and Training Center (PUSDIKLAT) Ragunan Jakarta. Data include nutritional status, eating disorder, menstrual disorder, and bone density. Assessment of nutritional status used BMI/A percentile and percent body fat; measurement of percent body fat used body fat analyzer HBF 200; assessment of eating disorder used eating disorder diagnostic scale; measurement of menstrual irregularity used questionnaire including frequency, menstrual cycle, menarche, and menstruation on last 3 months; and measurement of bone density used quantitative ultrasound bone densitometry. Result: Female athlete triad not found on subjects, but 15 subjects (23.1%) had bulimia and 1 subject (1.5%) had menstrual irregularity, i.e oligoamenorrhea, whereas bone density of all subjects (100%) normal, so that only 1 subject (1.5%) had two symptom of female athlete triad (bulimia and oligoamenorrhea).fifty six subjects (86,2%) had normal Â nutritional status. Based on fat body percent, that was found 1 subject (1.5%) having underfat, 10 subjects (15.4%) overfat, and 2 subjects (3.1%) obese. Conclusion:Female athlete triad not found in Education and Training Center (PUSDIKLAT) Ragunan Jakarta